THE EFFECT OF ALTERNATIVE TOURISM TRENDS ON THE VISITING DECISIONS OF MILLENIAL TOURISTS - Hary Hermawan; Titah Sholihah; Santosa; Dhimas Setyo Nugroho (Universitas Terbuka, 2021)
Tourism trends are starting to shift from being oriented towards mass tourism to alternative tourism. The tendency of tourists to back to nature, making ecotourism, is growing in interest. These changes can affect tourist decision making when visiting a tourism destination. The study aims to determine the effect of alternative tourism trends on millennial tourists visiting findings (a study of ecotourism destinations in Yogyakarta). Quantitative research was conducted by passing out questionnaires to 100 respondents who had seen the ecotourism destination in the Special Region of Yogyakarta (Ancient Volcano Nglanggeran, Mount Merapi Nation Park, and Mudal River Park). Sampling was done using cluster sampling and proportionate stratified random sampling techniques. Analysis using simple linear regression Based on the results of research at a significant level of 5% shows that alternative tourism trends have a positive and significant effect on the decision to visit millennial tourists (a study of ecotourism destinations in Yogyakarta). This is proved by the results of t-test analysis obtained at 4,966 > 1,665, then Ho is rejected, and Ha is accepted. Based on the results of the coefficient determination (RÂ²), an Adjusted R Square value of 0,201 shows that alternative tourism trends contributed 20,1% to the decision of visiting millennial tourists at ecotourism destinations in Yogyakarta.